Post-harvest of Anthurium andraeanum L. cv. Apalai foliage - Marsala, Juliana; Vieira Ferraz, Marcelo; Modenese Gorla da Silva, Silvia Helena; de Moraes Gomes Pereira, Danilo (Ornamental Horticulture, 2014)
Foliage stems of anthurium (Anthurium andraeanum L.) f. cv. Apalai were submitted to two experiments. In the first one, a pulsing solution with sucrose at concentrations of 0%, 2%, 4%, 6% and 8% were used, and in the second experiment, gibberellic acid sprays at concentrations of 0, 100, 200, 300 and 400 mg L-1, all experiments were kept at room temperature of 25 ºC and relative humidity of 75%. Sucrose treatment was not effective nor in the color maintenance neither in the stems weight, but for the gibberellic acid the best treatment applied was 200 mg L-1 concentration that maintained the higher scores. Treatment with gibberellic acid enabled efficient storage for 22 days.